The relationship of mental skills to performance on a tennis accuracy task under fatigued and non-fatigued conditions - Booras, M. C. (2001)
The purpose of this study was to determine whether athletes with higher mental skills perform tennis accuracy skills better than athletes with lower mental skills under two conditions. Division 1 tennis players (N = 11 men, N = 10 women) were divided into high and low mental skills groups by a median split on the ACSI-28. They were taken through two exercise conditions, fresh and fatigue, on two separate days and given a tennis accuracy task at the end of each condition. A repeated measure ANOVA determined there was no significant interaction between mental skill level and task condition scores. Overall, the low mental skill group had a 19% decrement during the fatigue condition compared to 9% for the high mental skill group. The task and exercise conditions of this study were sufficient for achieving fatigue and testing tennis accuracy, but were unable to differentiate between mental skill groups. Larger samples should be used in the future.